The Effect of Birthing Ball on the Smooth Process of Labor in Maternity Women at TPMB (Midwife Independent Practice) Purwakarta Regency, Indonesia - Angkut, Cik (HM Publisher, 2024)
The birthing process is a natural and physiological process, but it can be a tiring and painful process for the birth mother. One effort to help the birthing process run smoothly is to use a birthing ball. A birth ball is a large ball that is used for sitting, squatting, or turning around during the birthing process. This study aims to determine the effect of the birthing ball on the smoothness of the birthing process for mothers giving birth at TPMB (Midwife Independent Practice) Purwakarta Regency, Indonesia. This research uses a quasi-experimental method with a non-randomized control group design. The research sample was 60 primigravida mothers who were divided into two groups, namely the treatment group (30 mothers) and the control group (30 mothers). The treatment group was given a birthing ball during the birthing process, while the control group was not given a birthing ball. The results of the research show that there is an influence of the birthing ball on the smoothness of the birth process. Birthing mothers who used a birthing ball had a shorter active phase first stage time (p<0.05) and lower labor pain intensity (p<0.05) compared to birthing mothers who did not use a birthing ball. Based on the results of this research, it can be concluded that the birthing ball is an effective non-pharmacological method to help smooth the birthing process.